MODIFIED RADICAL MASTECTOMY: DEEP VERSUS SUPERFICIAL ERECTOR SPINAE BLOCK - A RANDOMIZED TRIAL. - Kumar, Santosh; Nath, Vikram; Kumar, Rahul (Student’s Journal of Health Research Africa, 2025)
Background The quality of life, recovery, and functionality of patients are adversely affected by the intense pain that often follows breast cancer surgery, such as a modified radical mastectomy. Objectives This study was conducted to assess the effectiveness and safety of superficial and deep erector spinae plane (ESP) blocks in individuals undergoing modified radical mastectomy. Materials and Methods It was a randomized-controlled pilot study that was conducted at Sri Krishna Medical College and Hospital, Muzaffarpur, Bihar, India. The study was conducted for one year, i.e., from September 2023 to August 2024. The study comprised 50 female patients. Results The average age of the fifty female participants in the study was 52 years. A consistent distribution of baseline clinical features and socioeconomic data was seen among the study groups. With a p-value < 0.05, the superficial ESP block group only lasted 04 hours before the first request for rescue analgesia; in contrast, the median length of 10 hours was significantly longer for the deep ESP block group. Conclusion This research shows that deep ESP blocks are more successful than superficial ESP blocks at lowering postoperative pain in patients having a modified radical mastectomy. Recommendations Deep ESP block is recommended for postoperative analgesia in mastectomy patients due to superior pain relief and reduced opioid use.